PLANTAS DE COBERTURA E SEUS EFEITOS NO CULTIVO DE CEBOLA EM BASES AGROECOLÓGICAS - BALDUINO, Barbara Chrys Gomes; MANOEL, Edmar; QUEVEDO, Lorislene; ESCOBAR, Mardileu; SILVA, Rógerio Ferreira da (ANAIS DO ENIC, 2018)
-